Efficacy and safety of regorafenib versus dinutuximab with chemotherapy in Chinese children with neuroblastoma (Bangladesh Journal of Pharmacology, 2019)
The objective of the present study was to evaluate the efficacy and safety of regorafenib in comparison with dinutuximab with chemotherapy in Chinese children with advanced neuroblastoma. The patients aged less than 16 years who were histologically diagnosed with advanced neuroblastoma were enrolled and randomized to receive either regorafenib plus best supportive care or dinutuximab plus chemotherapy plus best supportive care in a 1:1 ratio. The tumor response assessment was made in accordance with modified international neuroblastoma response criteria. Adverse events were also assessed. Regorafenib showed prolonged overall survival and progression-free survival than who received dinutuximab plus chemotherapy (overall survival: median 32.3 months versus 27.2 months; hazard ratio = 0.45; 95% CI 0.11-0.13, p